Cotinine inhibits TLR4/NF-κB signaling pathway and improves deep vein thrombosis in rats. Issue 6 (4th June 2020) - Cheng, Zhiyuan; Jia, Wei; Tian, Xuan; Jiang, Peng; Zhang, Yunxin; Li, Jinyong; Tian, Chenyang; Liu, Jianlong
Abstract: Background : The present study was designed to explore the regulatory mechanisms and influences of cotinine on deep vein thrombosis (DVT) in rats via the toll-like receptor 4/nuclear factor κ binding (TLR-4/NF-κB) pathway. Methods: In this experimental study, 30 SD rats were randomly assigned to control group, sham operation group, model group, cotinine (10 μg/kg) group, and model + cotinine (10 μg/kg) group. The thromboxane B2 (TXB2), 6-keto-PGF1α, plasminogen activator inhibitor (PAI), tissue plasminogen activator (t-PA), TLR4, NF-κB, and p65 mRNA and protein expression and tissue changes were analyzed by ELISA, Hematoxylin–Eosin (HE) staining, RT-PCR, and Western blot. Results: There was no significant difference between the control and sham operation groups ( P >0.05). The model and cotinine groups showed significantly higher mRNA and protein levels of TXB2, interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), PAI, TLR -4, and NF-κB, and significantly lower levels of 6-keto-PGF1α and t-PA than the control and sham operation groups ( P <0.05), and the model + cotinine group showed significantly higher mRNA and protein levels of TXB2, IL-6 and TNF-α, PAI, TLR -4, and NF-κB and significantly lower levels of 6-keto-PGF1α and t-PA than the model group ( P <0.05). Conclusion: Cotinine can aggravate thrombus and inflammation in rats with DVT, and the mechanism may be associated with the activation of the TLR-4/NF-κB inflammatory signaling pathway.